Civil legal interpretation of securing the fulfillment of an obligation using the neustoika (penalty) method (Texas Journal of Multidisciplinary Studies, 2023)
In this article, the issues of normative legal regulation regulating the penalty method of ensuring the fulfillment of obligations, as well as the concept and forms of neustoika are analyzed from a theoretical and legal point of view.